Biomimetic cell membrane-coated glucose/oxygen-exhausting nanoreactor for remodeling tumor microenvironment in targeted hypoxic tumor therapy. (November 2022) - Guo, Haoyu; Zhang, Weiyue; Wang, Lutong; Shao, Zengwu; Huang, Xin
Abstract: Hypoxia is a common feature within many types of solid tumors, which is closely associated with limited efficacy for tumor therapies. Moreover, the inability to reach hypoxic tumor cells that are distant from blood vessels results in tumor-targeting and penetrating drug delivery systems in urgent need. Here, glucose oxidase (GOX) and hypoxia-activated prodrug tirapazamine (TPZ) are loaded into photothermal conversion agent polydopamine (PDA) as the glucose/oxygen-exhausting nanoreactor named PGT. We further construct a tumor cell membrane-coated nanovesicle for the targeted delivery of PGT. This biomimetic nanovesicle exhibits significantly improved tumor-targeting and tumor-penetrating abilities. After internalization by the tumor cells, the loaded drug is quickly released in response to near-infrared (NIR) laser. The PGT nanoreactor can exhaust glucose and oxygen, and further enhance hypoxia within tumor, which efficiently inhibits hypoxic tumor by combining starvation therapy and hypoxia-activated chemotherapy. Mechanically, it is revealed that the nanoreactor significantly increases hypoxia level and downregulates the expression of hypoxia-inhibitory factor-1α (HIF-1α), thereby promoting T cell activation and macrophage polarization to remodel tumor immunosuppressive microenvironment. Therefore, this tumor microenvironment-regulable nanoreactor with sustainable and cascade targeted starvation-chemotherapy provides a novel insight into the treatment of hypoxic tumor.